IMPLEMENTATION OF INFORMATION TECHNOLOGY AND REGIONAL FINANCIAL MANAGEMENT TO IMPROVE THE QUALITY OF REGIONAL FINANCIAL STATEMENTS IN KARAWANG REGENCY - Via Selfiana; Sihabudin; Robby Fauji (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
This study aims to analyze the implementation of information technology and regional financial management in improving the quality of regional financial statements in Karawang Regency. The research used a qualitative method with data collection techniques including interviews, documentation, and observation. The results show that the application of integrated financial information systems such as SIPD and SIMDA has improved the efficiency, transparency, and accountability of financial management. The success of implementation is influenced by leadership support, infrastructure readiness, and the competency of human resources. Challenges include inconsistent data integration and technical constraints. The research highlights the importance of synergizing technology and financial governance to produce reliable, timely, and standard-compliant financial reports.